2000
DOI: 10.1007/pl00001709
|View full text |Cite
|
Sign up to set email alerts
|

Antennal glands in queen and worker of the fire ant, Solenopsis invicta Buren: first report in female social Aculeata (Hymenoptera, Formicidae)

Abstract: The antennae of the higher Hymenoptera (ants, bees and wasps) have been presumed to be exclusively sensory appendages, although the antennae of a number of the Parasitica also support a variety of glands. Using both SEM and TEM we show the presence of ectodermal glands in the antennae of workers and queens, but not in the males, of the Imported Fire Ant, Solenopsis invicta Buren. These glands and their associated pores are present on a glabrous proximal region of A9 of the antennae of workers and both A9 and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…Pores on the external surface are visible where canals from the antennal glands pass through the cuticle, as previously shown (Isidoro et al, 2000). Figures 1A and 1B show pores in workers and queens, respectively, near antennal segment joints.…”
Section: Resultssupporting
confidence: 78%
See 4 more Smart Citations
“…Pores on the external surface are visible where canals from the antennal glands pass through the cuticle, as previously shown (Isidoro et al, 2000). Figures 1A and 1B show pores in workers and queens, respectively, near antennal segment joints.…”
Section: Resultssupporting
confidence: 78%
“…In addition to the glands of the distal funiculus described here and previously (Isidoro et al, 2000), glands have been observed in the scape of three ant species: Eciton burchelli (Billen, 2000), and Polyergus rufescens and Formica cunicularia (Romani et al, 2006). Also, both type 1 and type 3 glands were observed in all antennomers except the scape of the primitive ant Dinoponera lucida (Marques-Silva et al, 2006).…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations